2002
DOI: 10.1074/jbc.m111935200
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD43 Enhances Human Immunodeficiency Virus Type 1 Transcriptional Activity and Virus Production That Is Induced upon TCR/CD3 Stimulation

Abstract: Human immunodeficiency virus type 1 (HIV-1) transcriptional activity is regulated by several cytokines and T cell activators. CD43 (sialophorin) is a sialoglycoprotein expressed on the surface of a wide variety of blood cells including T lymphocytes. Several studies have shown that CD43 ligation induces proliferation and activation of human T lymphocytes. We were thus interested in defining whether CD43-mediated signaling events can modulate the life cycle of HIV-1. We demonstrate here that CD43 cross-linking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 90 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…2A). It has already been reported that this signal can be the result of overlapping NF-B and NFAT complexes (3,4). The binding of NF-B was confirmed by supershift with anti-NF-B p50 antibodies ( Fig.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…2A). It has already been reported that this signal can be the result of overlapping NF-B and NFAT complexes (3,4). The binding of NF-B was confirmed by supershift with anti-NF-B p50 antibodies ( Fig.…”
supporting
confidence: 52%
“…An increasing number of accessory cell surface molecules are also involved in upregulation of T-cell activation (reviewed in reference 51). For example, we have recently demonstrated that CD43 functions as a potent costimulatory molecule for TCR/CD3-dependent induction of HIV-1 LTR-driven transcription and virus production (3). Another molecule of great interest in that respect is the intercellular adhesion molecule 3 (ICAM-3, or CD50), a 120-kDa, highly expressed cell surface antigen restricted to the leukocyte cell lineage (1,20,24).…”
mentioning
confidence: 99%
“…Recently, CD43-dependent signals were shown to enhance HIV type 1 transcriptional activity and virus production induced through TCR stimulation (48). Interestingly, Lck, and the scaffold proteins LAT and SLP-76 were all required for the HIV-1 transcriptional activity mediated through TCR and CD43 costimulation, suggesting a crucial role for Lck, LAT, and SLP-76 in the CD43-mediated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As a positive control, we used CD4 ϩ T cells (5 ϫ 10 6 ) that were activated for 3 days with PHA-L (1 g/ml) in the presence of rhIL-2 (30 U/ml) and stimulated for 4 h with OKT3 (1 g/ml) and anti-CD28 (1 g/ml) in a final volume of 2.5 ml of RPMI 1640. Cells were then washed twice with ice-cold PBS, and nuclear extracts were prepared according to a previously reported protocol (37). EMSAs were performed by incubating 10 g of nuclear proteins with 20 l of 1ϫ binding buffer (10 mM HEPES (pH 7.9), 4% glycerol, 1% Ficoll, 25 mM KCl, 1 mM DTT, 0.5 mM EDTA, 25 mM NaCl) containing 2 g of poly(dI-dC), 10 g of nuclease-free BSA fraction V, and 0.8 ng of a [␥-32 P]dsDNA oligonucleotide for 20 min at room temperature.…”
Section: Primary Naive and Memory Cd4mentioning
confidence: 99%